Effect of Type of Sugar and Dough Relaxation Time on the Shape Characteristics of Biscuits - Niroula, Anuj; Pokharel, Aastha; Acharya, Jyoti (Journal of Food Science and Technology Nepal, 2020)
This study was aimed to evaluate the effect of type of sugars namely dextrose, sucrose, sucrose-invert syrup mix, invert syrup and honey, and dough relaxation time of 15, 40, and 65 min. on the shape characteristics viz. width, thickness, spread ratio, and an expansion ratio of biscuits. The type of sugars significantly affected (p<0.05) all shape characteristics, while the dough relaxation only affected those of crystal sugars (sucrose and dextrose). High dough relaxation time enhanced the width of sucrose biscuits without significantly affecting (p>0.05) their thickness. In contrast, the thickness of dextrose biscuits decreased with increasing relaxation time. Liquid sugars (invert syrup and honey) enhanced the width of biscuits; the former enhancing the thickness as well. The study also demonstrated that a high spread ratio may also be associated with a low expansion ratio. Hence, both the spread ratio and expansion ratio must be considered when discussing the shape characteristics of biscuits with different ingredients.